2007
DOI: 10.2170/physiolsci.rp003507
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Thermal Stimulation, Applied to the Hindpaw via a Hot Water Bath, upon Ovarian Blood Flow in Anesthetized Nonpregnant Rats

Abstract: Abstract:The effects of thermal stimulation, applied to the hindpaw via a hot bath set to either 40°C (non-noxious) or 49°C (noxious), upon ovarian blood flow were examined in nonpregnant anesthetized rats. Ovarian blood flow was measured using a laser Doppler flowmeter. Blood pressure was markedly increased following 49°C stimulation. Ovarian blood flow, however, showed no obvious change during stimulation, although a small increase was observed after stimulation. Ovarian blood flow and blood pressure respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 23 publications
(34 reference statements)
1
4
0
Order By: Relevance
“…The decrease in ovarian blood flow by the electrical stimulation of the splanchnic nerve was completely abolished by the intravenous injection of alpha adrenoceptor antagonist. We also demonstrated that the electrical stimulation of the OPN decreases ovarian blood flow [11]. Our present study showed that an electrical stimulation of either the SON or the OPN produces a decrease in ovarian blood flow (ovarian venous plasma flow rate).…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…The decrease in ovarian blood flow by the electrical stimulation of the splanchnic nerve was completely abolished by the intravenous injection of alpha adrenoceptor antagonist. We also demonstrated that the electrical stimulation of the OPN decreases ovarian blood flow [11]. Our present study showed that an electrical stimulation of either the SON or the OPN produces a decrease in ovarian blood flow (ovarian venous plasma flow rate).…”
Section: Discussionsupporting
confidence: 68%
“…Autonomic nerves to the rat ovary reach the organ by two routes: the ovarian plexus nerve (OPN) along the ovarian artery and the superior ovarian nerve (SON) in the suspensory ligament [8,9]. We recently demonstrated that electrical stimulation of the splanchnic nerve or the OPN produces a vasoconstriction of ovarian arterioles and a reduction of ovarian blood flow in rats [10,11]. This result suggests a vasoconstrictor role of ovarian autonomic nerves in regulating ovarian blood flow.…”
mentioning
confidence: 99%
“…Noxious stimuli are transmitted to the cerebral cortex and perceived as “pain,” such information is integrated in the spinal cord and brain stem and influences autonomic nerve activity (somatoautonomic reflexes) [16]. Sympathetic nerve activity induced by noxious stimulation is thought to contribute to the onset and maintenance of some type of chronic pain [7].…”
Section: Introductionmentioning
confidence: 99%
“…In anesthetized rats, we examined the effects of NA and electrical stimulation of the autonomic nerves to the ovary on the diameter of ovarian arterioles, by use of digital video microscopy, and on ovarian blood flow, by use of laser Doppler flowmetry [ 21 , 22 ]. NA (5 μg/kg), injected intravenously into the jugular vein over 20 s resulted in a decrease in the diameter of ovarian arterioles and in ovarian blood flow, and an increase in mean arterial pressure (MAP) (Fig.…”
Section: Sympathetic Regulation Of Ovarian Blood Flowmentioning
confidence: 99%
“…The thin dashed vertical lines and the thick horizontal bars on the abscissae indicate the time of noradrenaline (NA) injection at 5 μg/kg ( c – e ) or the time of electrical stimulation of the ONP at 10 V and 50 Hz for 20 s ( h – j ). ( a – e , modified from Kanai et al [ 21 ]; f – j , modified from Uchida et al [ 22 ]) …”
Section: Sympathetic Regulation Of Ovarian Blood Flowmentioning
confidence: 99%